Analisis Tindak Tutur Ilokusi Bertema Vaksin dalam Saluran Youtube Reasearch of Community Mental Health Intiative - Nafikha Putri Arthamevia Maharani; Titis Abhirama Reswara; Yessi Ine Rahmandhani; Adhwa Farah Yosinta; Nadya Fransiska Julianti; Asep Purwo Yudi Utomo; Rossi Galih Kesuma; Ryan Hidayat (STIKes Ibnu Sina Ajibarang, 2025)
Illocutionary speech acts are actions of doing something with a specific purpose and function. Illocutionary speech acts as one of the main aspects of the study of speech. Acts are divided into five types, namely expressive, declarative, assertive, directive, and commissive speech acts. This research focuses its study on illocutionary speech acts in the Research of Community Mental Health Initiative's YouTube channel video playlist entitled